Building strong health supply chain systems: the visibility and analytics network approach to improving the Nigeria immunisation supply chain. Issue 4 (1st October 2018) - Ottih, Chibuzo; Cussen, Kevin; Mustafa, Mahmud
Abstract : Background: Health supply chain managers are unable to effectively monitor the performance of the immunisation supply chain in Nigeria. As a result, they are unable to make effective, data-driven decisions. This results in poor vaccine availability at some service delivery points. A lack of reliable data for evidence-based decision making is a significant contributor to this challenge. Method: The visibility and analytics network (VAN) principles were introduced to enable end-to-end visibility in the immunisation supply chain and logistics (ISCL) system and make more accurate data available to health supply chain managers. Results: The application of the VAN principles has led to improved data collection, real-time stock visibility and enhanced data analytics framework. This enhanced visibility has promoted a culture of accountability and data-driven decision-making, previously unattainable. Health supply chain managers are now equipped with better skills and tools to promote effective operation of the immunisation supply chain. Conclusion: The introduction of VAN principles has been an effective approach to improving data visibility and creating incremental improvements in the ISCL in Nigeria.